The developmental role of the stock market and the elements of Algiers stock market to achieve this role - zouda, amar (Milev Journal of Research and Studies, 2016)
stock markets perform active and distinctive economic functions in mobilizing savings and orienting them towards suitable and appealing investments. It is already known that the operation of stock markets is not void of difficulties and obstacles that hinder it from achieving its objectives especially under the conditions of economic globalization and financial crises facing it, and this is the situation facing Arab financial markets at present. The importance of the research has emerged from the significance of financial markets in contemporary economies for its effective contribution in fulfilling efforts of enhancing the process of economic development and improving investment climate. Thus; financial markets- Algeria stock market in particularshould meet the requirements of establishing efficient financial markets and seeking to cope up with current developments in international financial markets; which is aimed to by the research.